Gas hydrates immense energy potential and environmental challenges - Hester, Keith; SpringerLink (Online service). (London Springer, 2011)
Gas hydrates are both a huge energy resource and an environmental challenge. They have a significant impact on society because of their applications to the future of energy, protection of the environment and fuel transportation. Gas Hydrates opens up this fascinating, multidisciplinary field to non-specialists. It provides a scientific study of gas hydrates that considers their potential as an energy source while assessing the possible risk to the environment. The authors also examine the feasibility of using these natural compounds for storing and transporting gases such as methane and carbon dioxide. Diagrams and photos are used throughout Gas Hydrates to help readers understand the scientific and technical content. Each section has been designed so it can be read independently by academics and professionals in the oil and gas industry, as well as by all those with an interest in how hydrates combine to be an energy resource, an industrial challange and a geological hazard.
1. The Evolution of Energy Sources -- 2. The Clathrate Hydrates of Gases -- 3. The Structure and Formation of Gas Hydrates -- 4. Methods to Predict Hydrate Formation Conditions and Formation Rate -- 5. Physical Properties of Hydrates -- 6. Hydrates in Nature -- 7. Hydrates Seen as a Problem for the Oil and Gas Industry -- 8. Hydrates as an Energy Source -- 9. Industrial Applications -- 10. Environmental Issues with Gas Hydrates.
Electronic reproduction.
Keywords: Natural gas -- Hydrates; Electronic books